A Relationship Between Stress Level And Burnout Syndrome With Sleep Quality On Clinical Nursing Students In Faculty Of Nursing Universitas Airlangga - Rasyidah, Qurrata A'yuni; Fitryasari, Rizki; Wahyudi, Andri Setiya (Universitas Airlangga, 2020)
Introduction: Sleep is a basic need that must be fulfilled. Poor sleep quality can be caused by stress and fatigue. This study aims to analyze the relationship between stress levels and burnout syndrome with sleep quality on clinical nursing students of the Nursing Faculty at Universitas Airlangga.Method: This study uses a cross-sectional design. The population is clinical nursing student Faculty of Nursing Universitas Airlangga from the regular program and over the program level. The total sample was 126 respondents using a simple random sampling technique. Independent variables are stress level and burnout syndrome and the dependent variable is sleep quality. Data collected by questionnaires Perceived Stress Scale (PSS), Maslach Burnout Inventory (MBI) and Pittsburg Sleep Quality Index (PSQI) and then analyzed using spearmen's rho test and logistic regression test.Results: The results showed that there was a relationship between stress levels and sleep quality (p = 0,000, r = 0,311), there was a relationship between burnout syndrome specifically the dimensions of emotional exhaustion with sleep quality (p = 0,025) and the results of logistic regression tests showed a correlation between stress levels (p = 0,000) and burnout syndrome dimensions of emotional exhaustion (p = 0.025) with the quality of sleep in clinical nursing students of the Faculty of Nursing Universitas Airlangga.Conclusion: The level of stress experienced by clinical nursing students, especially stress in caring for patients and burnout syndrome, especially in the dimensions of emotional exhaustion affect the quality of sleep for clinical nursing students.